My teacher is a robot - Brown, Jeffrey, 1975- (Crown Books for Young Readers, 2019)
From the author of the "New York Times"-bestselling Jedi Academy books comes an imaginative picture book about a kid whose creative outlook has everyone at school seeing the world through new eyes. Fred does not want to go to school because it's boring. Especially since he thinks his teacher is a robot. If only Fred could imagine a way for his day to be more exciting...